Utilization of Provider-Initiated HIV Testing and Counseling as an Intervention for PMTCT Services Among Pregnant Women Attending Antenatal Clinic in a Teaching Hospital in Ethiopia - Gebresillassie, Begashaw Melaku; Emiru, Yohannes Kelifa; Erku, Daniel Asfaw; Mersha, Amanual Getnet; Mekuria, Abebe Basazn; Ayele, Asnakew Achaw; Tegegn, Henok Getachew (Frontiers in Public Health, 2019)
Purpose: Little is known about acceptance of provider-initiated HIV testing and counseling (PICT) as an intervention for prevention of mother to child transmission of HIV (PMTCT) in many parts of sub-Saharan Africa including Ethiopia. This study aimed at assessing the utilization and acceptance rate of PICT as an intervention for PMTCT among pregnant women attending University of Gondar referral and teaching hospital (UoGRTH), Ethiopia. Methods: A hospital-based cross-sectional study was conducted on 364 pregnant women attending antenatal care clinic at UoGRTH through an interviewer-administered questionnaire. Frequencies, means, and percentages were used to report different variables. Univariate analysis and multivariate logistic regression analysis were used to come up with factors associated with acceptance of PICT services. Results: Out of 364 respondents, 298 330 (81.7%) of them accepted provider-initiated HIV testing and counseling. Rural residency (AOR: 364, 95% CI: 2.17–6.34), higher educational status (AOR: 3.15, 95% CI: 1.86–6.82), planning of HIV test disclosure to male partners (AOR: 7.81, 95% CI: 3.17–13.14), and a higher average monthly income (AOR: 4.01, 95% CI: 2.32–7.61) were found to be strong predictors of acceptance of provider-initiated HIV testing and counseling. Conclusions: The present study revealed a higher rate of acceptance of PICT among pregnant women. Enhancing access to and consistent use of antenatal care service among pregnant women and encouraging the active involvement of male partners are recommended to further increase the uptake of provider-initiated HIV testing and counseling.